Keabsahan Hibah Tanah kepada Anak Angkat melalui Perspektif Hukum Perdata di Indonesia - Sahid, Kheeisya Arzeeta S (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Land grants to adopted children are an important legal issue in the context of civil law in Indonesia. This study aims to analyze the validity of grants given to adopted children and their legal implications. According to Article 1866 of the Civil Code, a grant is a grant made by the grantor to the recipient of the grant without compensation. In the context of adopted children, even though they are not related by blood to the adoptive parents, their legal status is recognized as equal to that of biological children, so grants given to them can be considered valid as long as they meet the formal and material requirements established by law. However, there are legal challenges related to the implications of land grants to adopted children, especially when other heirs are involved. The grant deed made by the Land Deed Making Officer (PPAT) must consider the approval of other heirs so as not to cause disputes in the future. This study uses normative juridical methods to explore various regulations governing grants and the rights of adopted children in the context of inheritance. The results of the study show that while grants for adopted children can be made, it is important to pay attention to the legality aspects and potential conflicts that may arise as a result of the cancellation of the grant by the adoptive parents or claims from other heirs